Education Loan Repayment Intention - Vaicondam, Yamunah; Huey Wen, Onn (International Journal of Psychosocial Rehabilitation, 2020)
Education loans are one of financial aid that designed to help students to pay their tuition fee, purchase learning materials and supplies on top of funding their living expenses in higher educational institutions. Majority of the students graduating with debt and the debt level are snowballing by years which are unmanageable by graduates while facing repayment years. Malaysia is one of the countries with high loan defaulter’s rate. Although the recent trends have shown an increase in reimbursement, it is not sufficient to sustain the funds needed for the future graduates. Besides, studies are lacking among private universities participants. This study adapted the Theory of Reasoned Action (TRA) by Fishbein which is mainly to predict the attitudinal influence and behavioural intention in education loan repayment. This descriptive study employed 380 participants who graduates from private universities in Klang Valley to determine the factors that influenced the intention to make repayment of education loan. The OLS pooled regression shows that the independent variables commitment, attitude and affordability have significant positive effect on the education loan repayment intention, however the fear of penalization is insignificant to the intention to make repayment of education loan in Malaysia. Further studies are encouraged to compare the intention among students in public and private higher education institution in Malaysia due diverse funding requirement and price of tuition fee.